PCHŁA I DZIEŃ DOBRY JOHNA DONNE’A − SŁOWO, KTÓRE STAŁO SIĘ CIAŁEM - Gładkowska, Dorota (Acta Neophilologica, 2017)
This article reveals the exceptional union of two metaphysical poems by John Donne, so far regarded as separate entities. By conducting a thorough linguistic analysis, the author gradually shows subtle links between The good-morrow and The Flea on the lexical, thematic, and structural levels. Their existence provides evidence that J. Donne’s works may form meaningful assemblages and should therefore be interpreted only in the context of the whole manuscript. The Flea and The good-morrow clearly comment on one another and together complete the vision of the world which emerges from their verses. Thanks to their autotelic character – the material form that itself conveys a message − the reader experiences this lyrical diptych as an observable phenomenon and an intellectual puzzle. The poet deliberately breaks existing patterns and rules to expose chosen elements. It is the irregularities in the composition of the verses and stanzas, frequently perceived as imperfections, that open the door to deeper levels of his metaphysical concept.